The Past in the (Lost) Memory of the Roma - Mojžišová, Zuzana (Poznańskie Studia Slawistyczne, 2023)
This study uses authentic interviews from field research into the Roma people of Slovakia to search for partial answers to questions concerning the functioning of collective and individual memory of the marginalised ethnic group that to this day almost exclusively leans on oral presentation instead of written recordings when sharing stories and experiences between generations. Witnesses to wartime events are dying out. Their stories need to be reinterpreted. They are too often lost, however, in the chasm of oblivion caused by ostracisation, neglected education, politics and, above all, poverty. The state has failed in the past and continues to fail today, albeit differently, by enabling the process of forgetting.